Israel's Academic Arena The Colleges and University Extensions Revolution - Haliwa, Pinhas (Peter Lang International Academic Publishing Group, 2021)
Following mounting political and social pressures to increase public accessibility to higher education in Israel, in 1994 Israel's academic arena was transformed from a monolithic system consisting exclusively of research universities to a binary one comprised of both research universities and academic colleges. Within the system's expansions plans, Israel's Council for Higher Education prioritized the increased accessibility of higher education to peripheral populations, defining this as a central aim. This transformation was achieved in a short period of time through regional colleges that operated in the periphery and offered professional academic courses. In addition to these institutions, a number of University Extensions operated in Israel, founded based on the American Protestant Colleges model, introduced in Israel in the 1960's by Bar Ilan University. In 2000 all these institutions were officially included in the country's higher education system, resulting in a huge increase in the total number of students in academia, with higher education becoming accessible to the country's social and geographic periphery. This book reviews the evolution of Israel's academic system and examines the ways in which it has met the national aims defined by the Council for Higher Education in its plans.